Informatics in schools : fundamentals of computer science and software engineering : 11th International Conference on Informatics in Schools: Situation, Evolution, and Perspectives, ISSEP 2018, St. Petersburg, Russia, October 10-12, 2018, Proceedings /: fundamentals of computer science and software engineering : 11th International Conference on Informatics in Schools: Situation, Evolution, and Perspectives, ISSEP 2018, St. Petersburg, Russia, October 10-12, 2018, Proceedings. (2018) - Unknown
No abstract available